Organic Solvent‐free Asymmetric 1, 4‐Addition in Liquid‐ or Solid‐State using Conventional Stirring Catalyzed by a Chiral Rhodium Complex Developed as a Homogeneous Catalyst. Issue 23 (23rd October 2020) - Korenaga, Toshinobu; Kori, Hiroto; Asai, Shota; Kowata, Ryo; Shirai, Masayuki
Abstract: Organic solvent‐free asymmetric 1, 4‐addition of arylboronic acids to enone substrates was performed by using a chiral rhodium complex catalyst developed as a homogeneous catalyst. Reactions catalyzed by [RhOH(cod)]2 with chiral diphosphine ligands in liquid‐ or solid‐state proceeded to give chiral 1, 4‐adducts in high yield with enantioselectivities up to ca. 100 % ee by conventional stirring without mechanochemistry such as ball milling. The solid‐state reactions under a static condition also proceeded, but with a slight decrease in enantioselectivity of the 1, 4‐adduct. SEM observations of the solid‐state reactions indicated that no nanoparticles catalyst was generated. The organic solvent‐free reaction could be applied to gram‐scale synthesis by performing a greener purification using a minimum necessary organic solvent. Abstract : Enantioselective Catalysis : Organic solvent‐free asymmetric 1, 4‐addition of arylboronic acids to enone substrates using chiral metal complex catalysts developed as homogeneous catalysts was performed. Smooth and highly enantioselective solid‐state reactions were accomplished with conventional stirring without special activation methods.